Globular clusters: DNA of early-type galaxies? - Forte, Juan Carlos (2014)
This paper explores if the mean properties of early-type galaxies (ETGs) can be reconstructed from 'genetic' information stored in their globular clusters (GCs; i.e. in their chemical abundances, spatial distributions and ages). This approach implies that the formation of each globular occurs in very massive stellar environments, as suggested by some models that aim at explaining the presence of multipopulations in these systems. The assumption that the relative number of GCs to diffuse stellar mass depends exponentially on chemical abundance, [Z/H], and the presence of two dominant GC subpopulations (blue and red), allows the mapping of low-metallicity haloes and of higher metallicity (and more heterogeneous) bulges. In particular, the masses of the low-metallicity haloes seem to scale up with dark matter mass through a constant. We also find a dependence of the GC formation efficiency with the mean projected stellar mass density of the galaxies within their effective radii. The analysis is based on a selected subsample of galaxies observed within the ACS Virgo Cluster Survey of the Hubble Space Telescope. These systems were grouped, according to their absolute magnitudes, in order to define composite fiducial galaxies and look for a quantitative connection with their (also composite) GCs systems. The results strengthen the idea that GCs are good quantitative tracers of both baryonic and dark matter in ETGs.